DELAYED GRAFT FUNCTION FOLLOWING LAPAROSCOPIC LIVE DONOR NEPHRECTOMY: A MULTIVARIATE ANALYSIS - Tirtayasa, Pande Made Wisnu; Situmorang, Gerhard Reinaldi; Rodjani, Arry; Rasyid, Nur (Indonesian Urological Association, 2016)
Objective: This study was performed to define and investigate the incidence, risk factors, and clinical characteristics of delayed graft function (DGF) in laparoscopic live donor nephrectomy (LDN). Material & methods: We retrospectively analyzed the medical records of donor and recipient from our first 100 cases of laparoscopic LDN in Cipto Mangunkusumo General Hospital Jakarta, from November 2011 to February 2014. The criteria used to define DGF were the requirement for dialysis in postoperative week 1 and/or serum creatinine greater than 2.5 mg/dl at postoperative day 7. Patients who did not match any of these criteria were define as having normal renal allograft function. Results: The overall prevalence of DGF was 14%. Recipients body mass index, cold ischemia time, vascular anastomosis time, and total ischemia time were higher among the delayed graft function group, but no risk factors for DGF were significantly associated after multivariate analysis. Conclusion: The incidence of DGF in our study was in the range of that observed in previous studies. The factors that previously reported and believed as risk factors of DGF in laparoscopic LDN were not significantly associated with the development of DGF in our study.